Sheep rearing in Sweden : a niche with agroecological potential - Högele, Leonie (SLU/Dept. of Biosystems and Technology (from 130101), 2022)
Sheep production in Sweden is an agricultural sector that today exists merely as a small niche, despite its agroecological potential. Through literature research, a survey and 18 semi-structured interviews, this paper defines the sector’s marginality and attempts to explain it. The effects of the sector’s marginality on the sustainability of Swedish sheep farming and agriculture as a whole are evaluated. Finally, desirable directions for development of the Swedish sheep sector are suggested. The findings showed that the marginality of the Swedish sheep sector to a large extent is a product of socio-cultural factors that affect the structure of the sheep sector. Not least, the sector’s marginality reinforces itself. In addition, bio-physical, historical and political circumstances have played a role in marginalising the sector. Several weaknesses and strengths regarding sustainability were recognized within the current, small-scale structures of Swedish sheep farming. Opportunities were identified through which the sheep sector could actually contribute to agricultural sustainability precisely through its marginality. Equally, threats to sustainability that arise from the sector being limited to its niche were acknowledged. Overall, the findings suggest that it would be beneficial for the Swedish sheep sector to grow if agroecological, sustainable farming is the ultimate goal. Whether this growth can and will be achieved, however, is questionable.